2021
DOI: 10.33774/chemrxiv-2021-47tqn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amide-to-ester substitution as a strategy for optimizing PROTAC permeability and cellular activity

Abstract: Bifunctional PROTAC degraders belong to "beyond Rule of 5" chemical space, and criteria for predicting their drug-like properties are underdeveloped. PROTAC components are often combined via late-stage amide couplings, due to the reliability and robustness of amide bond formation. Amides, however, can give rise to low cellular permeability and poor ADME properties. We hypothesized that a bioisosteric replacement of an amide with a less polar ester could lead to improvements in both physicochemical properties a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 74 publications
0
37
0
Order By: Relevance
“…Based on the presented DMS data, for instance exemplified by VHL P71I and VHL H110L , it is conceivable that ARV-771 induces a ternary complex of a different geometry than the ones previously resolved for MZ1 10 or macroPROTAC-1 37 , or the one we here resolve for AT2. In support of these predictions, are the observations that (i) ARV-771-induced ternary complex assemblies that involve VCB and BET bromodomains have thus far proven to be unsuccessful to crystallization efforts; (ii) ARV-771 and MZ1 displayed distinct intra-BET bromodomain cooperativity profiles in FP ternary complex assays 51 . Hence, this and related observations emerged from this study together underscore that nuanced, differentiated mutational profiles and sensitivities can arise even with degraders which share otherwise highly similar chemical structures, mechanisms, and cellular activities.…”
Section: Discussionmentioning
confidence: 81%
“…Based on the presented DMS data, for instance exemplified by VHL P71I and VHL H110L , it is conceivable that ARV-771 induces a ternary complex of a different geometry than the ones previously resolved for MZ1 10 or macroPROTAC-1 37 , or the one we here resolve for AT2. In support of these predictions, are the observations that (i) ARV-771-induced ternary complex assemblies that involve VCB and BET bromodomains have thus far proven to be unsuccessful to crystallization efforts; (ii) ARV-771 and MZ1 displayed distinct intra-BET bromodomain cooperativity profiles in FP ternary complex assays 51 . Hence, this and related observations emerged from this study together underscore that nuanced, differentiated mutational profiles and sensitivities can arise even with degraders which share otherwise highly similar chemical structures, mechanisms, and cellular activities.…”
Section: Discussionmentioning
confidence: 81%
“…It is interesting to note that all esters ( 22–25 ) are more potent than their respective amide counterparts ( 18–21 ) by between 2- and 126-fold in DC 50 (Table ). Recently, we have shown that the amide-to-ester substitution can provide a simple strategy to increase the PROTAC degradation activity due to increased lipophilicity and cellular permeability while maintaining remarkable intracellular stability . This trend is well reflected in this compound set, as all esters ( 22–25 ) were cell-active and showed more potent DC 50 and a prominent hook effect at the higher concentrations compared to their amide counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…29 In accordance with this observation, the lesser dipole embedded within 1,2,4-oxadiazoles led to reductions in EPSA on the order of Δavg = -12±9 when compared to matched amide counterparts. We found that N-methylation (Δavg = -12±5) 30 , 31 and ester substitution (Δavg = -15±9) 32,33 were among the simplest and most effective tactics to reduce the EPSA of amide-containing compounds, a finding presaged by the abundance of these groups in naturally occurring, permeable macrocyclic peptides. 34 Thus, among common amide bioisosteres that preserve the parent group's HBA capacity while removing its donor function, only 1,2,3-triazoles failed to reliably reduce EPSA.…”
Section: Amidesmentioning
confidence: 97%